"It feels like something difficult is coming back to haunt me": An exploration of 'meltdowns' associated with autistic spectrum disorder from a parental perspective. (January 2018) - Montaque, Indiana; Dallos, Rudi; McKenzie, Becky
The research explored the experience and understandings expressed by parents of children with autism concerning 'meltdowns', which are commonly described as distressing, escalating episodes of conflicts. Semi-structured interviews were conducted with six parents of children with a diagnosis of autism regarding their experience of 'meltdowns'. Parents were asked to track the process of the meltdowns as well as to describe their experiences. Three over-arching themes emerged which encapsulated their experience: Living in Dread: Anxiety and fear of escalating patterns, Attempting to Correct for Negative Childhood Experiences and Condemnation from the Self and Others. The findings suggested that the meltdowns were perceived as having an escalating and predictable process, that parents anticipated meltdowns with anxiety, experienced feelings of helplessness and felt condemned by others. Importantly, it also appeared that parents' responses were influenced by their own childhood experiences of parenting and that they attempted to 'correct' these to be better parents. A model of the meltdowns is suggested along with a discussion of clinical implications for early intervention with families.